2023
DOI: 10.1007/s11030-023-10634-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on structural insights of MAO-B inhibitors: a review on target-based approach

Abstract: Parkinson’s disease is a neurodegenerative disorder characterized by slow movement, tremors, and stiffness caused due to loss of dopaminergic neurons caused in the brain’s substantia nigra. The concentration of dopamine is decreased in the brain. Parkinson’s disease may be happened because of various genetic and environmental factors. Parkinson’s disease is related to the irregular expression of the monoamine oxidase (MAO) enzyme, precisely type B, which causes the oxidative deamination of biogenic amines such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 118 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…MAO-A and MAO-B inhibition prevents the breakdown of neurotransmitters and increases their respective concentrations in the synaptic cleft for neuronal signaling. Several classes of antidepressants are available (Figure 5) which include atypical antidepressants, monoamine oxidase inhibitors (MAOIs), serotoninnorepinephrine reuptake inhibitors (SNRIs), and SSRIs (Baweja et al, 2023;Dwyer & Bloch, 2019;Mannan et al, 2022;Nandi et al, 2023). Suryawanshi et al reported the rationale designing followed by synthesis and in silico studies of phenylacetamides derivatives (16a-y) as antidepressant agents.…”
Section: Mechanism Of Action Of Antidepressantsmentioning
confidence: 99%
“…MAO-A and MAO-B inhibition prevents the breakdown of neurotransmitters and increases their respective concentrations in the synaptic cleft for neuronal signaling. Several classes of antidepressants are available (Figure 5) which include atypical antidepressants, monoamine oxidase inhibitors (MAOIs), serotoninnorepinephrine reuptake inhibitors (SNRIs), and SSRIs (Baweja et al, 2023;Dwyer & Bloch, 2019;Mannan et al, 2022;Nandi et al, 2023). Suryawanshi et al reported the rationale designing followed by synthesis and in silico studies of phenylacetamides derivatives (16a-y) as antidepressant agents.…”
Section: Mechanism Of Action Of Antidepressantsmentioning
confidence: 99%
“…The therapeutic capability of MAO's inhibitors, in conjunction with an exhaustive knowledge of the 3D structure of the MAO-B active site, may contribute to significant improvement in the development of novel drugs for Parkinson's disease. Recent updates on the design, synthesis, and clinical trials of new MAO candidates have been summarized in the paper of Baweja GS et al [13]. Even though numerous compounds have been continuously synthesized and clinically tested as possible candidates for treating PD, the dietary restrictions and adverse effects developed urgently require new theoretical, experimental, and therapeutic strategies to overcome these shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, cheminformatics approaches are systematically used in the early stages of drug development projects [11][12][13][14][15][16][17][18][19][20][21][22] and environmental science to assist the experiment in order to expedite and save resources and costs [23][24][25][26][27][28]. In silico tools can contribute significantly to exploring side effects by handling off-target interactions, which necessitates a thorough knowledge of structural information about off-target proteins [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations